Physical activity and exercise alter cognitive abilities, and brain structure and activity in obese children - Shao, Xueyun; Tan, Li Hai; He, Longfei (Frontiers in Neuroscience, 2022)
The prevalence of childhood obesity is increasing to such an extent that it has become a major global public health problem in the 21st century. Obesity alters children’s brain structure and activity and impairs their cognitive abilities. On the basis of these findings, it is necessary for educational and healthcare institutions to combat childhood obesity through preventive and therapeutic strategies. In general, exercise and physical activity are considered common but effective methods for improving physical, psychological, and brain health across the life span. Therefore, this review article mainly focuses on existing neuroimaging studies that have used magnetic resonance imaging (MRI), and functional magnetic resonance imaging (fMRI)to assess children’s brain anatomy and neural activity. We intended to explore the roles of physical activity and exercise in modulating the associations among childhood obesity, cognitive abilities, and the structure and activity of the brain.